Decision Support System Determines The Quality Of The House In Pringsewu District Using The WASPAS Method - Elisabet Yunaeti Anggraeni; Riki Renaldo; Tri Susilowati (Tech-E, 2021)
The quality of the Flats is a concern of every citizen and related health offices who need healthy flats. To determine the quality of a flat is declared healthy or unhealthy, three criteria are used, including: housing components, housing facilities, and behavior. In this study, 5 samples were used to determine the quality of the flats, from the calculation results obtained 2 houses that were declared healthy and 3 houses were declared unhealthy. The WASPAS method is applied to determine the quality priority of healthy flats. In this study, researchers used several criteria including area, environment, infrastructure, location, security. The alternatives in this study are, Flat A, Flat B, Flat C, Flat D and Flat E. From these calculations, the results obtained from the analysis determine a healthy apartment using the WASPAS (Weight Aggregated Sum Product Assessment) method. The following: 1. Flat A gets a score of 6.0144, 2. Flat B gets a score of 6.0117, 3. Flat C gets a score of 5.5871, 4. Flat E gets a score of 5.1253. 5. Apartment D received a score of 4,8253.5. From the calculation results, the WASPAS method can be an input for the related health offices to follow up on the priority of healthy flats so that it is easier for people to choose healthy flats.